Rationale for a Behavioral Clinical Approach to Routinely Prescribing Prism. - Warshowsky, Joel H. (Optometry & Visual Performance, 2019)
Background: The application of prism is a challenging clinical question. Prism prescription for the reme-diation of routine visual dysfunction has not been widely used in optometric and/or oph-thalmological practice. In general, prisms are most often prescribed as a last resort. This is rationalized because precise methodology for prescribing an appropriate amount and ori-entation of prism has not been conclusively determined. This paper presents a rationale and process for routinely prescribing and managing therapeutic prism within a pediatric population. Prism application and its clinical effect on horizontal and vertical imbalance as well as its influence on vestibular, proprioception, and visual motor function will be con-sidered. The benefits of prescribing lateral horizontal, vertical, and yoked prism will be presented in a therapeutic and clinical oriented approach. Case Reports: Case presentations will demonstrate before and after clinical results, using various modes of prism application. In each case presentation, outcomes demonstrate improved ocular motor function, improved awareness of body in space, and a greater sense of self-awareness. Each case presented will demonstrate a patient's apparent increase in self-esteem through a greater sense of their environment as a consequence of their ability to create improved awareness and subsequent movement through space (egocentric process). Conclusion: The behavioral concept of vision considers any ophthalmic lens application potentially to provide the ability to achieve an alteration of human behavior. The use of prisms emphasizes a lens' effect on posture and balance through one's center of gravity and ultimately one's body orientation in space. It potentially enhances one's ability to rematch eye coordination in relation to coordination of one's body in space. This paper presents the argument that a lens incorporating a prism component can routinely result in a more effi-cient, effective, and effortless visual, motor, and behavioral change, without resulting in prism adaptation.